2018
DOI: 10.1371/journal.pone.0192269
|View full text |Cite
|
Sign up to set email alerts
|

The genetic heterogeneity of Arab populations as inferred from HLA genes

Abstract: This is the first genetic anthropology study on Arabs in MENA (Middle East and North Africa) region. The present meta-analysis included 100 populations from 36 Arab and non-Arab communities, comprising 16,006 individuals, and evaluates the genetic profile of Arabs using HLA class I (A, B) and class II (DRB1, DQB1) genes. A total of 56 Arab populations comprising 10,283 individuals were selected from several databases, and were compared with 44 Mediterranean, Asian, and sub-Saharan populations. The most frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 76 publications
10
55
0
Order By: Relevance
“…In regard to the HLA‐B allele lineages in the UAE, the three most frequent were B*51 (0.163), B*08 (0.137) and B*50 (0.137), which is similar to the HLA‐B frequencies for 373 Arabs from the UAE reported by Valluei et al (). HLA‐B*51 also occurs at high frequency (>0.15) in the population of Saudi Arabia (Hajeer et al, ), Oman (Albalushi et al, ) and Iraq (Abbas, ), is intermediate (0.10 to 0.15) in Ghana, Lebanon, Libya, Jordan and Europe (Hajjej et al, ), and relatively low (<0.10) in Singapore, Indonesia, Australia and South Africa (Verity, Wallace, Vaughan, & Stanford, ). Although the prevalence of Behcet's disease in UAE Arabs, and particularly the Bedouin, is not known, it has been associated strongly with HLA‐B*51 in the population of Turkey, Israel, Iran, Saudi Arabia, Iraq and Japan, and those along the historic Silk Road (Keino & Okada, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In regard to the HLA‐B allele lineages in the UAE, the three most frequent were B*51 (0.163), B*08 (0.137) and B*50 (0.137), which is similar to the HLA‐B frequencies for 373 Arabs from the UAE reported by Valluei et al (). HLA‐B*51 also occurs at high frequency (>0.15) in the population of Saudi Arabia (Hajeer et al, ), Oman (Albalushi et al, ) and Iraq (Abbas, ), is intermediate (0.10 to 0.15) in Ghana, Lebanon, Libya, Jordan and Europe (Hajjej et al, ), and relatively low (<0.10) in Singapore, Indonesia, Australia and South Africa (Verity, Wallace, Vaughan, & Stanford, ). Although the prevalence of Behcet's disease in UAE Arabs, and particularly the Bedouin, is not known, it has been associated strongly with HLA‐B*51 in the population of Turkey, Israel, Iran, Saudi Arabia, Iraq and Japan, and those along the historic Silk Road (Keino & Okada, ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta‐analysis of HLA class I and class II genes of 100 populations from 36 Arab and non‐Arab countries by Hajjej et al () confirmed the genetic heterogeneity of some Arab populations and suggested that Arabs could be stratified into four groups: (1) North Africans (Algerians, Tunisians, Moroccans and Libyans), (2) Levatine Arabs (Palestinians, Jordanians, Lebanese and Syrians), and two different Arabian Peninsula clusters, (3) a Saudis, Kuwaitis and Yemenis cluster, and (4) an Omanis, Emiratis and Bahrainis cluster. In our phylogenic analysis (Figure and Figure ), the Saudi, UAE and Omani populations of the Arabian Peninsula were in the same clade as 4 different Pakistani sub‐populations and separate to an adjoining clade of Jordanians, Israeli Jews, Tunisians and Moroccans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified the MHC class II alleles expected to recognize the salivary protein epitopes and investigated the predominant alleles of human populations living in Egypt and Jordan. The MHC class II alleles with strong binding affinities for PpSP12 that are also prevalent in Egyptian and Jordanian human populations include: DRB1_0301, DRB1_040X, DRB1_110X, DRB1_1301, and DRB1_150X [6769]. The MHC class II alleles identified for PpSP14 include: DRB1_1101, DRB1_0301, DRB1_040X, DRB1_11XX, DRB1_13XX, DRB1_15XX, and to a lesser extent DRB1_070X [6769].…”
Section: Discussionmentioning
confidence: 99%
“…The MHC class II alleles with strong binding affinities for PpSP12 that are also prevalent in Egyptian and Jordanian human populations include: DRB1_0301, DRB1_040X, DRB1_110X, DRB1_1301, and DRB1_150X [6769]. The MHC class II alleles identified for PpSP14 include: DRB1_1101, DRB1_0301, DRB1_040X, DRB1_11XX, DRB1_13XX, DRB1_15XX, and to a lesser extent DRB1_070X [6769]. The six remaining salivary proteins are predicted to bind to MHC class II alleles with varying affinity.…”
Section: Discussionmentioning
confidence: 99%